New structure of step-up DC-DC converter based on three winding coupled inductor with high gain capability featuring integrated renewable energy applications - Pouneh Aghakhanlou; Fatemeh Falahi; Ali Nadermohammadi; Hasan Sarikhan; Seyed Hossein Hosseini; Naghi Rostami; Mehran Sabahi (Scientific Reports)
Abstract This research presents an innovative design for a non-isolated DC-DC converter, which utilizes a single switch in a high step-up configuration. The key element of this design is a three-winding coupled inductor (TWCI), which plays a crucial role in achieving a substantial voltage increase. By utilizing a low duty cycle, the converter minimizes conduction losses in the power switch, resulting in enhanced efficiency. The converter offers several benefits, including reduced voltage stress on both power switches and diodes, a common ground, high efficiency, a simple structure and control mechanism, and fewer components. The study thoroughly examines the converter’s operational modes and provides a comparison with other types of converters to highlight its distinctive characteristics. To validate the converter’s performance, a 400 W prototype was developed and tested in the lab, operating with a 20 V input, a 260 V output, and a switching frequency of 50 kHz.